Interpretation of aeromagnetic data using GIS to evaluate the geotectonic regime of the Sabinas Basin - Jose Alberto Batista; Yuri Almaguer Carmenates; Josue D. Martínez González (Earth Sciences Research Journal, 2017)
The study present the use of Geographic Information System (GIS) to assess the geotectonic regimen of the Sabinas Basin. Initially, the GIS database was designed using geological and geophysical information (total magnetic field reduced to the pole). Subsequently, 2D models of the basin were obtained along 4 profiles running on a north-south direction. The implementation of GIS enables a geological-geophysical interpretation generating various thematic maps that overlap the magnetic map during interpretation. The analysis of overlapping maps enables the identification of areas with different geotectonic regimes in the Sabinas Basin, as well as the relationship between these environments and mineralization. The qualitative and quantitative interpretation of the aeromagnetic data obtained for the total magnetic field reduced to the pole delineate uplifted basement areas as well as shallower blocks within them. This paper presents the location of both the basin´s deepest zones and its probable faults, which can be linked to the block boundaries. The faults zones and block boundaries correspond to the main mineral deposits found in the basin. Finally, the geotectonic regime of some sectors of the basin is detailed in order to reaffirm the results obtained by the interpretation of aeromagnetic data.